Can the Gains from International Diversification Be Achieved without Trading Abroad? - Errunza, Vihang; Hogan, Ked; Hung, Mao‐Wei (Journal of Finance, 1999)
ABSTRACT We examine whether portfolios of domestically traded securities can mimic foreign indices so that investment in assets that trade only abroad is not necessary to exhaust the gains from international diversification. We use monthly data from 1976 to 1993 for seven developed and nine emerging markets. Return correlations, mean‐variance spanning, and Sharpe ratio test results provide strong evidence that gains beyond those attainable through home‐made diversification have become statistically and economically insignificant. Finally, we show that the incremental gains from international diversification beyond home‐made diversification portfolios have diminished over time in a way consistent with changes in investment barriers.